2022
DOI: 10.1021/acsabm.2c00180
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase-Mimicking Activity of Biogenic Gold Nanoparticles Produced from Prunus nepalensis Fruit Extract: Characterizations and Application for the Detection of Mycobacterium bovis

Abstract: In the present study, a facile, eco-friendly, and controlled synthesis of gold nanoparticles (Au NPs) using Prunus nepalensis fruit extract is reported. The biogenically synthesized Au NPs possess ultra-active intrinsic peroxidase-like activity for the oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) in the presence of H 2 O 2 . Chemical analysis of the fruit extract demonstrated the presence of various bioactive molecules such as amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…The dithiothreitol (DTT) reduction method was used to prepare IgG antibodies containing sulfhydryl groups, with minor modifications from previously reported protocols (Ji et al, 2010). In short, a 200 μL solution of IgG antibody (QUBMA-Bov) produced previously (Das et al, 2022;Stewart et al, 2012) was prepared at a concentration of 1 mg/mL in PBS 0.1 M -EDTA 2 mM buffer. 8 μL of DTT 0.5 M prepared in aqueous solution was then added and the mixture incubated under gentle stirring for 25 min at RT.…”
Section: Functionalisation Of Aunstmentioning
confidence: 99%
See 1 more Smart Citation
“…The dithiothreitol (DTT) reduction method was used to prepare IgG antibodies containing sulfhydryl groups, with minor modifications from previously reported protocols (Ji et al, 2010). In short, a 200 μL solution of IgG antibody (QUBMA-Bov) produced previously (Das et al, 2022;Stewart et al, 2012) was prepared at a concentration of 1 mg/mL in PBS 0.1 M -EDTA 2 mM buffer. 8 μL of DTT 0.5 M prepared in aqueous solution was then added and the mixture incubated under gentle stirring for 25 min at RT.…”
Section: Functionalisation Of Aunstmentioning
confidence: 99%
“…Their assay also showed positive results for samples containing high numbers of M. bovis cells (≥10 4− 5 CFU/g) in line with the sensitivity values reported herein. More recently, ferromagnetic AuNP (Gilbride et al, 2021) and biogenic AuNP (Das et al, 2022) have been used to develop colourimetric assays, improving the LOD values reported above. These systems, however, still rely on expensive lab-based readout equipment, while at the same time cannot escape the limited robustness of immunoassays for detecting small bacterial concentrations.…”
Section: Sensitivity and Selectivitymentioning
confidence: 99%
“…Liu et al (2015) reported that platinum NPs exhibited catechol oxidase like activity [11] . Das et al (2022) synthesized gold NPs using Prunus nepalensis fruit extract which can mimic peroxidase like activity and used for the detection of Mycobacterium bovis [12] . Rasheed et al (2020) reported catalase like activity of iron oxide and manganese oxide NPs [13] .…”
Section: Introductionmentioning
confidence: 99%
“…[11] Das et al (2022) synthesized gold NPs using Prunus nepalensis fruit extract which can mimic peroxidase like activity and used for the detection of Mycobacterium bovis. [12] Rasheed et al (2020) reported catalase like activity of iron oxide and manganese oxide NPs. [13] Nanoparticles such as gold, Fe 3 O 4, ZnO, TiO 2 show peroxidase activity in the presence of hydrogen peroxide via electron transfer method.…”
Section: Introductionmentioning
confidence: 99%
“…Nanozymes are a type of nanomaterial with enzyme-like properties, which combines the advantages of nanomaterials with natural enzymes, and thus have attracted widespread attention. [1][2][3] Since Fe 3 O 4 as a nanozyme was reported for the first time, 2 various nanomaterials with peroxidase-like activities have been developed, 3 including noble metals, [4][5][6] transition metal oxides [7][8][9] and carbon-based materials. [10][11][12] However, many shortcomings hinder the application of metalbased nanozymes, such as high cost (noble metals), lack of specificity (transition metal oxide) and health risk (V 2 O 5 ).…”
Section: Introductionmentioning
confidence: 99%